A simulation model for evaluating facilities' adaptability in the fare collection area of subway stations. Issue 4 (January 2017) - Xianyu, Wu
Abstract: According to relative position between ticket office and automatic fare gates, the facility layout of a fare collection area can be classified into three types. The application of these facility layout types are analyzed in the 15 subway hubs and 85 general stations, Beijing. According to the analysis results of facility layout and passenger flow line, fare collection area can be classified into 9 functional subareas. The adjacency degree is defined as the location relationship between adjacent subareas. Secondly, the simulation model is developed with an individual passenger as the object, to update an individual passenger's status. And the moving behavior model of an individual passenger is developed based on the macro pedestrian flow model according to traffic characteristics of many passengers in the field data. In status updating, the average speed of the passengers in different simulation time varied with the density in the subarea. In the case study the facility configurations of the fare collection system in the rail transit hub, DongZhiMen are evaluated with the proposed model for the adaptability of the facility configuration in the fare collection systems. Results show that the provided simulation model is effective and valuable for facility layout optimization and adaptability analysis.